General Public Perception of Social Media, Impact of COVID-19 Pandemic, and Related Misconceptions. (15th July 2023) - Ali, Rabiya; Jawed, Shireen; Baig, Mukhtiar; Azam Malik, Ahmad; Syed, Fatima; Rehman, Rehana
Abstract: Objectives: This research aimed at investigating the general public perception of social media (SM), impact of COVID-19 (SARS-CoV-2) pandemic, and related misconceptions among the Pakistani population. Methodology: Cross-sectional study conducted during the peak of COVID-19 in Pakistan between May and June, 2020 comprised of 2307 Pakistani male and female participants. Subjects under 18 years of age and nationality other than Pakistani were excluded. An online questionnaire was administered via the Internet using various kinds of social media. Results: The study was comprised of 2307 male and female participants; 2074 (89.90%) used SM for seeking COVID-19 information, 450 (20%) used both Facebook (FB) and WhatsApp (WA), and 267 (11.6%) used FB, WA, Twitter, and Instagram. Respondents' perceptions showed that: 529 (23%) believed in SM information and 1564 (67.8%) stated that COVID-19 affected their social and mental wellbeing. Respondents' knowledge revealed that: 1509 (65.40%) had poor knowledge (≤ 50% score), and 798 (34.6%) had good knowledge (> 50% score) ( P < 0.001) about COVID-19. Binary logistic regression analysis showed that higher-earning positively correlated, while private jobs were negatively associated, with good knowledge. Conclusion: FB and WA were the 2 common social media used by study participants (a third had good knowledge). COVID-19 affected the social, mental, and psychological well-being of individuals. Good knowledge was greater in individuals with higher earning and less with private job involvements.